PENGARUH BRAND TRUST, HARGA, DAN CUSTOMER ENGAGEMENT TERHADAP KEPUTUSAN PEMBELIAN LOKAL BRAND KECANTIKAN DI KABUPATEN SUMBAWA - Santoso, Agus; Purnama, Yuni (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the influence of brand trust, price, and customer engagement on the purchasing decisions of local cosmetic products in Sumbawa Regency. Using a quantitative approach and purposive sampling technique, data were collected from 102 Generation Z respondents through an online questionnaire. The data were analyzed using multiple linear regression. The results indicate that all three independent variables have a positive and significant effect on purchasing decisions. Brand trust emerged as the most dominant factor, followed by customer engagement and price. These findings suggest that marketing strategies emphasizing brand trust, customer engagement, and competitive pricing are essential in capturing the Generation Z market, particularly in non-metropolitan areas like Sumbawa. Local cosmetic brands produced by large companies such as PT Paragon, which already enjoy a strong reputation, are the preferred choice among Generation Z in Sumbawa. This highlights that corporate image remains a key factor in building consumer trust.